Syntabulin–Kinesin-1 Family Member 5B-Mediated Axonal Transport Contributes to Activity-Dependent Presynaptic Assembly - Cai, Qian (J Neurosci, 2007)
The mechanism by which microtubule-based axonal transport regulates activity-dependent presynaptic plasticity in developing neurons remains mostly unknown. Our previous studies established that syntabulin is an adaptor capable of conjoining the kinesin family member 5B (KIF5B) motor and syntaxin-1. We now report that the complex of syntaxin-1–syntabulin–KIF5B mediates axonal transport of the active zone (AZ) components essential for presynaptic assembly. Syntabulin associates with AZ precursor carriers and colocalizes and comigrates with green fluorescent protein (GFP)-Bassoon-labeled AZ transport cargos within developing axons. Knock-down of syntabulin or disruption of the syntaxin-1–syntabulin–KIF5B complex impairs the anterograde transport of GFP-Bassoon out of the soma and reduces the axonal densities of synaptic vesicle (SV) clusters and FM4-64 [N-(3-triethylammoniumpropyl)-4-(p-dibutylaminostyryl)pyridinium, dibromide] loading. Furthermore, syntabulin loss of function results in a reduction in both the amplitude of postsynaptic currents and the frequency of asynchronous quantal events, and abolishes the activity-induced recruitment of new GFP-Bassoon into the axons and subsequent coclustering with SVs. Consequently, syntabulin loss of function blocks the formation of new presynaptic boutons during activity-dependent synaptic plasticity in developing neurons. These studies establish that a kinesin motor–adaptor complex is critical for the anterograde axonal transport of AZ components, thus contributing to activity-dependent presynaptic assembly during neuronal development.